2015
DOI: 10.1038/srep17187
|View full text |Cite
|
Sign up to set email alerts
|

Capturing complex tumour biology in vitro: histological and molecular characterisation of precision cut slices

Abstract: Precision-cut slices of in vivo tumours permit interrogation in vitro of heterogeneous cells from solid tumours together with their native microenvironment. They offer a low throughput but high content in vitro experimental platform. Using mouse models as surrogates for three common human solid tumours, we describe a standardised workflow for systematic comparison of tumour slice cultivation methods and a tissue microarray-based method to archive them. Cultivated slices were compared to their in vivo source ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 31 publications
9
123
2
Order By: Relevance
“…Murine NSCLC tumours and clinical specimens were precision‐cut to make 200‐μm slices with a VT1200S microtome (Leica Biosystems, Wetzlar, Germany), as described previously . Murine slices were transferred to rotating incubators (Alabama Research & Development, Munford, AL, USA) (supplementary material, Figure S2A), within 90–120 min after mice had been killed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine NSCLC tumours and clinical specimens were precision‐cut to make 200‐μm slices with a VT1200S microtome (Leica Biosystems, Wetzlar, Germany), as described previously . Murine slices were transferred to rotating incubators (Alabama Research & Development, Munford, AL, USA) (supplementary material, Figure S2A), within 90–120 min after mice had been killed.…”
Section: Methodsmentioning
confidence: 99%
“…Precision‐cut tumour slices, which capture the native tumour in its microenvironment, constitute an attractive model with which to address this need. Within the IMI‐PREDECT project (http://www.predect.eu), we developed a workflow for short‐term culture of tumour slices, and showed that organotypic supports and atmospheric oxygen are strict requirements for tissue viability . A number of other studies have shown that responses to cytotoxic agents or selected targeted compounds can be modelled in clinical tumour‐derived slices .…”
Section: Introductionmentioning
confidence: 99%
“…The results for Ki-67, phospho-AKT, and phospho-STAT3 staining were determined by two independent experts under the same condition. For quantification, the sections of each immunostaining were scored using the method of histochemical score (H-score), which was calculated as the product of percentage of stained cells and intensity of staining [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…Primary tumour tissues from biopsy or surgical resection can be embedded in ECM and cultured as an in vitro model [30][31][32][33][34] (figure 2a). The embedded tumour sections retain the tumour vasculature, nearby stroma and the heterogeneity of the tumour cells.…”
Section: Ex Vivo Tumour Culturementioning
confidence: 99%